Effectiveness of Oncologist‐Referred Exercise and Healthy Eating Programming as a Part of Supportive Adjuvant Care for Early Breast Cancer. (5th October 2017) - Kirkham, Amy A.; Van Patten, Cheri L.; Gelmon, Karen A.; McKenzie, Donald C.; Bonsignore, Alis; Bland, Kelcey A.; Campbell, Kristin L.
Abstract : Background: Randomized trials have established efficacy of supervised exercise training during chemotherapy for breast cancer for numerous health outcomes. The purpose of this study was to assess reach, effectiveness, maintenance, and implementation of an evidence‐based exercise and healthy eating program offered within an adjuvant care setting. Subjects, Materials, and Methods : Women receiving adjuvant chemotherapy for breast cancer were given a prescription by their oncologist to participate in the Nutrition and Exercise during Adjuvant Treatment (NExT) program. The NExT program consisted of supervised, moderate‐intensity, aerobic and resistance exercise three times a week during adjuvant therapy, followed by a step‐down in supervised sessions per week for 20 additional weeks, plus one group‐based healthy eating session. Usual moderate‐to‐vigorous physical activity (MVPA) and health‐related quality of life (HRQoL) were assessed by questionnaire at baseline, program completion, and one year later, along with measures of satisfaction and safety. Results : Program reach encompassed referral of 53% of eligible patients, 78% uptake ( n  = 73 enrolled), and 78% retention for the 45.0 ± 8.3‐week program. During the program, MVPA increased (116 ± 14 to 154 ± 14 minutes per week, p  = .014) and HRQoL did not change. One year later, MVPA (171 ± 24 minutes per week, p  = .014) and HRQoL (44 ± 1 to 49 ± 1, p  < .001) were significantly higher than baseline. Exercise adherence was 60% ± 26% to three sessions per week during treatment. No major adverse events occurred and injury prevalence did not change relative to baseline. Participants were highly satisfied. Conclusion: This oncologist‐referred exercise and healthy eating supportive‐care program for breast cancer patients receiving chemotherapy was safe, successful in reaching oncologists and patients, and effective for improving MVPA and maintaining HRQoL. Implications for Practice: Despite evidence that exercise is both safe and efficacious at improving physical fitness, quality of life, and treatment side effects for individuals with cancer, lifestyle programming is not offered as standard of cancer care. This study describes an oncologist‐referred, evidence‐based exercise and healthy eating program offered in collaboration with a university as supportive care to women with breast cancer receiving chemotherapy. The program was well received by oncologists and patients, safe, and relatively inexpensive to operate. Importantly, there was a significant positive impact on physical activity levels and health‐related quality of life lasting for 2 years after initiation of therapy. Abstract : The Nutrition and Exercise during Adjuvant Treatment (NExT) study was designed to assess the effectiveness of a supervised exercise and healthy eating program offered as part of supportive care in a real‐world setting for breast cancer patients receiving adjuvant chemotherapy. Reach, effectiveness, maintenance, and implementation were assessed, and the results are reported here.